Rhizodeposition under drought and consequences for soil communities and ecosystem resilience - Preece, Catherine; Peñuelas, Josep (Plant and soil, 2016)
Background Rhizodeposition is the release of organic compounds from plant roots into soil. Positive relationships between rhizodeposition and soil microbial biomass are commonly observed. Rhizodeposition may be disrupted by increasing drought however the effects of water stress on this process are not sufficiently understood. Scope We aimed to provide a synthesis of the current knowledge of drought impacts on rhizodeposition. The current scarcity of well-defined studies hinders a quantitative meta-analysis, but we are able to identify the main effects of water stress on this process and how changes in the severity of drought may produce different responses. We then give an overview of the links between rhizodeposition and microbial communities, and describe how drought may disrupt these interactions. Conclusions Overall, moderate drought appears to increase rhizodeposition per gram of plant, but under extreme drought rhizodeposition is more variable. Concurrent decreases in plant biomass may lessen the total amount of rhizodeposits entering the soil. Effects on rhizodeposition may be strongly species-dependant therefore impacts on soil communities may also vary, either driving subsequent changes or conferring resilience in the plant community. Advances in the study of rhizodeposition are needed to allow a deeper understanding of this plant-soil interaction and how it will respond to drought.